Preparation and characterization of thiosemicarbazide functionalized graphene oxide as nanoadsorbent sheets for removal of lead cations - Hassan, A. F.; Bulánek, Roman (Springer, 2019)
A facial and novel method for removal of Pb+2 based on the appealing interaction between thiosemicarbazide-modified graphene oxide nanosheets and Pb+2 is reported in this work. Textural and chemical characterization of graphite, graphene oxide, esterified graphene oxide and thiosemicarbazide-modified graphene oxide nanosheets was investigated using thermogravimetric analysis (TGA), nitrogen adsorption at - 196 degrees C, transmission electron microscopy (TEM), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). Adsorption of Pb+2 was confirmed by Langmuir model with maximum adsorption capacity of 192.7 mg/g for thiosemicarbazide-modified graphene oxide nanosheets at 27 degrees C and initial pH value of 5.0. Kinetic studies showed that the adsorption of lead ions on the solid adsorbents follows pseudo-first order and Elovich kinetic models. Regeneration of graphene oxide, esterified graphene oxide and thiosemicarbazide-modified graphene oxide nanosheets was studied using different eluents (H2O, 0.1 M HCl, 0.1 M EDTA) at different pH values. Both of disodium salt of ethylenediaminetetraacetic acid (EDTA) and HCl solutions (0.1 M) are efficient eluents to desorb lead cations from the solid adsorbent surface. Desorption efficiency of HCl solution decreases with increasing its pH value.
Příprava a charakterizace nanodestiček grafen-oxidu funkcionalizovaného thiosemicarbazidem pro odstranění olovnatých kationtů
Keywords: Adsorption; Characterization; Environmental; Kinetics; Nanomaterials; adsorpce; charakterizace; environmentální; kinetika; nanomateriály